Case Report: Recurrent blepharal kaposiform hemangioendothelioma in an adult patient - Liu, Wei; Zhao, Dan; Zhou, Shirui; Chen, Hong (Frontiers in Surgery, 2024)
BACKGROUND： Kaposiform hemangioendothelioma (KHE) is a rare and invasive vascular tumor that mainly occurs in children, rarely seen in adults. We report a case of KHE found on the eyelid of an adult patient.CASE REPORT： An adult patient with KHE recurred half year after tumor resection. He underwent second surgical resection and intraoperative chemotherapy. There was no evidence of recurrence at the three-year follow-up.CONCLUSION： Adult KHE is easy to be misdiagnosed. KHE can be treated by surgical resection. Complete resection of the tumor and intraoperative chemotherapy may help prevent a recurrence.